Differential equations, difference equations and fuzzy logic in control of dynamic systems - Usenik, Janez (JET on-line, 2016)
In this article, the use of certain mathematical tools to create a dynamic system control is described; such a control could be applied to a power supply system. In continuous dynamic systems, the control of the system is described by one or more differential equations; however, in discrete dynamic systems, this control is described by one or more difference equations. Both differential and difference equations are highly effective tools in conventional mathematical analysis. In the previous twenty years, algorithmic principles of fuzzy logic in the control of the dynamic systems have been very useful. In this article, the applications of all three approaches are presented. In the case of the fuzzy logic approach, there is an example of the energy efficiency in the employment of biomass with an emphasis on developing the environmental sustainable biomass index.
Keywords: diferencialne enačbe; diferenčne enačbe; difference equations; differential equations; dinamični sistemi; dynamic system; fuzzy logic; Laplace transform; mehka logika; z-transform